A Rare Class of New Dimeric Naphthoquinones from Diospyros lotus have Multidrug Reversal and Antiproliferative Effects - Rauf, Abdur; Uddin, Ghias; Siddiqui, Bina S.; Molnár, Joseph; Csonka, Ákos; Ahmad, Bashir; Szabó, Diana; Farooq, Umar; Khan, Ajmal (Frontiers in Pharmacology, 2015)
Three new dimeric naphthoquinones, 5,4′-dihydroxy-1′-methoxy-6,6′-dimethyl-7,3′-binaphthyl-1,4,5′,8′-tetraone (1), 5′,8′-dihydroxy-5-methoxy-6,6′-dimethyl-7,3′-binaphthyl-1,4,1′,4′-tetraone (2) and 8,5′,8′-trihydroxy-6,6′-dimethyl-7,3′-binaphthyl-1,4,1′,4′-tetraone (3), were isolated from the roots of Diospyros lotus. Their structures were elucidated by spectroscopic techniques, including 1D and 2D NMR, such as HSQC, HMBS, NOESY and J resolved. Compounds 1-3 were evaluated for their effects on the reversion of multidrug resistance (MDR) mediated by P-glycoprotein through use of the rhodamine-123 exclusion screening test on human ABCB1 gene transfected L5178Y mouse T-cell lymphoma. Compounds 1-3 were also assessed for their antiproliferative and cytotoxic effects on L5178 and L5178Y mouse T-cell lymphoma lines. Both 1 and 2 exhibited promising antiproliferative and MDR-reversing effects in a dose dependent manner. The effects of the tested compounds on the activity of doxorubicin were observed to vary from slight antagonism to antagonism.